Label-free high-throughput screening via acoustic ejection mass spectrometry put into practice - Winter, Martin; Simon, Roman P.; Häbe, Tim T.; Ries, Robert; Wang, Yuting; Kvaskoff, David; Fernández-Montalván, Amaury; Luippold, Andreas H.; Büttner, Frank H.; Reindl, Wolfgang (SLAS discovery, 2023)
Acoustic droplet ejection-open port interface-mass spectrometry (ADE-OPI-MS) is a novel label-free analytical technique, promising to become a versatile readout for high-throughput screening (HTS) applications. The recent introduction of ADE-OPI-MS devices to the laboratory equipment market, paired with their compatibility with laboratory automation platforms, should facilitate the adoption of this technology by a broader community. Towards this goal, instrument robustness in the context of HTS campaigns - where up to millions of samples in complex matrices are tested in a short time frame - represents a major challenge, which explains the absence of detailed literature reports on this subject. Here, we present the results of our first fully automated HTS campaign, based on the ADE-OPI-MS technology, aiming to identify inhibitors of a metabolic enzyme in a >1 million compound library. The report encompasses the assay development and validation steps, as well as the adaptation for HTS requirements, where refinement of the capillary cleaning concept was crucial for final success. Altogether, our study unequivocally demonstrates the applicability of the ADE-OPI-MS technology for HTS-based drug discovery.